Implementasi Teknologi Informasi dan Komunikasi New Media Digital sebagai Konsep Model Pembelajaran Siswa di SMPN 101 Jakarta - Rayung Wulan (SAP (Susunan Artikel Pendidikan), 2023)
After the Covid-19 pandemic, various parts of the world began to pursue and experience improvements in the world of education, the learning concept that provides various facilities makes students look for something that makes it easy and understandable for the material conveyed by the teacher in the learning model. Digital Information and Communication Technology New Media offers a very interesting learning concept among students, new application platforms have sprung up to facilitate learning such as mentorship, Quizizz, profs and others. The purpose of this study is to see and know the concept of a learning model that can be easily understood by students at SMPN 101 Jakarta. As is known, in the last two years students have been presented with a learning model that makes students understand without being able to understand the concept of the learning model as a whole. The method used was quantitative with a comparative causal approach using a field survey with 94 students at SMPN 101 Jakarta. Testing the truth of the hypothesis of 94 student respondents at SMPN 101 Jakarta with a simple linear regression analysis. The results obtained can be seen based on research data that new digital media has a great influence on the concept of learning models 71.3% and 63.8% of the concept of learning models with the help of digital media. It can be seen that new digital media information and communication technology is very helpful in determining the concept of student learning models at SMPN 101 Jakarta.